2008
DOI: 10.1021/jp075814h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Antioxidant Action of Silybin and 2,3-Dehydrosilybin Flavonolignans: A Joint Experimental and Theoretical Study

Abstract: Flavonolignans from silymarin, the standardized plant extract obtained from thistle, exhibit various antioxidant activities, which correlate with the other biological and therapeutic properties of that extract. To highlight the mode of action of flavonolignans as free radical scavengers and antioxidants, 10 flavonolignans, selectively methylated at different positions, were tested in vitro for their capacity to scavenge radicals (DPPH and superoxide) and to inhibit the lipid peroxidation induced on microsome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
156
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(183 citation statements)
references
References 36 publications
24
156
2
1
Order By: Relevance
“…In previous studies, the inherent hepatoprotective and antioxidant activity of silymarin was shown to be caused by its control of free radicals (FR), which are produced by the hepatic metabolism of toxic substances such as Et-OH, acetaminophen (Paracetamol), or carbon tetrachloride. The FR damage cellular membranes and cause lipoperoxidation (LPO) [19] . The cytoprotective effect in liver is also caused by the inhibition of the cyclooxygenase cycle, leukotrienes, and the production of FR in Kupffer cells in mice.…”
Section: Overviewmentioning
confidence: 99%
“…In previous studies, the inherent hepatoprotective and antioxidant activity of silymarin was shown to be caused by its control of free radicals (FR), which are produced by the hepatic metabolism of toxic substances such as Et-OH, acetaminophen (Paracetamol), or carbon tetrachloride. The FR damage cellular membranes and cause lipoperoxidation (LPO) [19] . The cytoprotective effect in liver is also caused by the inhibition of the cyclooxygenase cycle, leukotrienes, and the production of FR in Kupffer cells in mice.…”
Section: Overviewmentioning
confidence: 99%
“…The antioxidant effects of silibinin have been showed in several cell studies. Silibinin is classified as an antioxidant compound because it blocks radical formation, binds many radical species (scavenger), interferes with lipid peroxidation mechanisms of membranes, and then increases the intracellular content of scavengers [60] . Gomez et al [61] in 2010 investigated the role of Viusid as an antioxidant and an immunomodulator in nonresponder HCV infected patients.…”
Section: Silymarin Complexmentioning
confidence: 99%
“…[20][21][22] However, the theoretical aspects of the free radical scavenging mechanism of phenolic antioxidants remains an important subject for the accurate prediction of free radical scavenging activity in physiological environments. [23][24][25][26][27] As a free radical, O 2 ·− is an important biological intermediate in living cells, 28) and is overproduced in tissues subjected to chronic infection and inflammation. 29) O 2 ·− causes oxidative DNA damage in living tissues under inflammatory conditions.…”
mentioning
confidence: 99%